Pendidikan Multikultural Untuk Mencegah Bullying Etnosentrisme di Pondok Pesantren - Daulay, Irmasani; Hidayat, Rahmat; Harahap, Sumper Mulia (Penerbit Widina, Widina Media Utama, 2025)
Ethnocentrism-based bullying is one of the social problems that can occur in Islamic boarding school environments. As a religious-based educational institution, Islamic boarding schools have an important role in integrating the values of multiculturalism to create an environment of harmony and mutual understanding and respect. This article aims to analyze the implementation of multicultural education in preventing ethnocentrism bullying in Islamic boarding schools. Through literature research, this article identifies multicultural education strategies based on the values of tolerance, justice and respect for diversity. The results of the discussion show that multicultural education can be carried out through the development of an inclusive curriculum, teacher training, and strengthening the value of togetherness in the daily lives of students.ABSTRAKBullying berbasis etnosentrisme merupakan salah satu permasalahan sosial yang dapat terjadi di lingkungan pondok pesantren. Sebagai lembaga pendidikan berbasis keagamaan, pesantren memiliki peran penting dalam mengintegrasikan nilai-nilai multikulturalisme untuk menciptakan lingkungan yang harmonis dan saling menghormati. Artikel ini bertujuan untuk menganalisis implementasi pendidikan multikultural dalam mencegah bullying etnosentrisme di pondok pesantren. Melalui penelitian pustaka, artikel ini mengidentifikasi strategi pendidikan multikultural berbasis nilai-nilai toleransi, keadilan, dan penghormatan terhadap keragaman. Hasil pembahasan menunjukkan bahwa pendidikan multikultural dapat dilakukan melalui pengembangan kurikulum inklusif, pelatihan guru, dan penguatan nilai kebersamaan dalam kehidupan sehari-hari santri.